CD 117 Immunoexpression in Invasive Breast Carcinoma: Association with various prognostic parameters - Raikar, Poornima; Kumar, B Deepak; V, Srinivasa Murthy (Annals of Pathology and Laboratory Medicine, 2018)
Background: CD 117 (Cluster Differentiation 117), encoded by the proto-oncogene C-Kit is a transmembrane tyrosine kinase growth factor receptor which inhibits apoptosis and potentiates cell proliferation. In normal breast epithelium, c-kit is highly expressed; however, its expression is low or completely lost in primary invasive breast carcinoma, suggesting its role in breast carcinogenesis. Objective: To evaluate the expression of CD 117 in invasive breast carcinoma and to study its association with various prognostic factors. Materials and Methods: Fifty cases of invasive breast carcinoma of different histological types and grades were evaluated for CD117 immunoexpression and the association of the same was studied with respect to various prognostic factors, ER/PR receptor status and Her2/neu status. Results: A statistically significant association was seen between negative expression of CD 117 with increased age (p=0.04), higher tumor grade (p=0.02), positive hormone receptor status (ER; p=0.001, PR; 0.005), negative Her2/neu (p=0.006) and tumors having a microvascular density of more than 19 per high power field (p-0.01). Conclusion: CD 117 immunoexpression, either negative or positive in invasive breast carcinoma has to be reported on a routine basis as a negative expression projects the prognosis of breast carcinoma patients and a positive expression will identify patients for a potential therapeutic intervention.